Relative contribution of the presence of an estuarine dam and land reclamation to sediment dynamics of the Nakdong Estuary - Chang, Jongwi; Lee, Guan-hong; Harris, Courtney K.; Figueroa, Steven Miguel; Jung, Nathalie W. (Frontiers in Marine Science, 2023)
The Nakdong Estuary of Korea is a dramatic example of an urban estuary that has been heavily developed with the installation of two estuarine dams and approximately 17 km2 of tidal flat reclamation. This study aims to understand the relative contribution of the different physical alterations by implementing four model simulations of the COAWST modeling system: (1) present condition, (2) pre-estuarine dam construction, (3) pre-tidal flat reclamation, (4) both pre-estuarine dam construction and pre-reclamation. In Cases 2 and 4, the model grid was modified to extend the Nakdong estuary upriver about 60 km and remove the estuarine dam. In Cases 3 and 4, the model grid was modified to restore the reclaimed tidal flats. All simulations shared the same initial conditions, boundary conditions, and forcing. Then, the simulation results for current velocity, suspended sediment concentration (SSC), and deposition were used to estimate the relative contribution of each alteration. The results showed that the annual, depth-averaged currents for the pre-estuarine dam (Case 2) were 80% faster than the present condition but were 10% slower for Case 3 (no land reclamation case). Likewise, the depth-averaged SSC was higher by about 25 mg/L in the estuary for Case 2, but it was reduced by about 9 mg/L for Case 3. The increase of velocity and SSC for Case 2 resulted from the removal of the estuarine dam, which changed both the tidal properties (tidal amplitude was reduced by about 40 cm) and estuarine circulation (factor of 5 reductions in the vertical salinity gradient), while the decrease for Case 3 was induced by the reduction in sediment accommodation space (15% of water volume) without a change in the circulation. These results also revealed that the estuarine dam enhanced deposition more than the land reclamation that showed very little change. The changes in current velocity, SSC, and deposition for Case 4 (no dam/reclamation) were very similar to Case 2. Overall, this study suggests that the influence of the estuarine dam was larger than that of the land reclamation in the altered Nakdong Estuary. Moreover, the combination of estuarine alterations acted to enhance the effects. These findings can serve as analogs that can be applied to other estuaries where various human alterations have occurred.